2016
DOI: 10.3109/19396368.2016.1159748
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics: The future of microdissection TESE?

Abstract: Non-obstructive azoospermia (NOA) is a severe form of infertility accounting for 10% of infertile men. Microdissection testicular sperm extraction (microTESE) includes a set of clinical protocols from which viable sperm are collected from patients (suffering from NOA), for intracytoplasmic sperm injection (ICSI). Clinical protocols associated with the processing of a microTESE sample are inefficient and significantly reduce the success of obtaining a viable sperm population. In this review we highlight the sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 70 publications
(79 reference statements)
0
25
0
1
Order By: Relevance
“…Additionally, sperm cryopreservation is a critical part of assisted reproductive technology (ART) (Araki et al, 2015; Tomita et al, 2016; Zou et al, 2013), while most of the applications of microfluidics in sperm processing were focused on sorting or isolation of sperm from semen sample; few studies were found on CPA addition and removal (Cho et al, 2003; Huang et al, 2014; Li et al, 2016; Samuel et al, 2016; Sano et al, 2010; Schuster et al, 2003). Fortunately, both the designs for the staggered herringbone microfluidic mixer (Park et al, 2012) and the passive, planar micromixer based on logarithmic spirals (Scherr et al, 2015; Scherr et al, 2012) (Figure 7E), which are initially developed for sperm activation, can be potentially adopted for CPA processing, since where controllable extracellular mixing is supplied.…”
Section: Controllable Addition and Removal Of Cpasmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, sperm cryopreservation is a critical part of assisted reproductive technology (ART) (Araki et al, 2015; Tomita et al, 2016; Zou et al, 2013), while most of the applications of microfluidics in sperm processing were focused on sorting or isolation of sperm from semen sample; few studies were found on CPA addition and removal (Cho et al, 2003; Huang et al, 2014; Li et al, 2016; Samuel et al, 2016; Sano et al, 2010; Schuster et al, 2003). Fortunately, both the designs for the staggered herringbone microfluidic mixer (Park et al, 2012) and the passive, planar micromixer based on logarithmic spirals (Scherr et al, 2015; Scherr et al, 2012) (Figure 7E), which are initially developed for sperm activation, can be potentially adopted for CPA processing, since where controllable extracellular mixing is supplied.…”
Section: Controllable Addition and Removal Of Cpasmentioning
confidence: 99%
“…Significant progress has been made in recent years for application of microfluidics in ART, e.g., sperm activation, sorting and isolation, oocyte processing, fertilization, and embryo culture (Cho et al, 2003; de Wagenaar et al, 2016; Huang et al, 2014; Li et al, 2016; Ohta et al, 2010; Samuel et al, 2016; Sano et al, 2010; Scherr et al, 2015; Schuster et al, 2003; Suh et al, 2003; Tsai et al, 2010; Zhang et al, 2011b). As an important and indispensable part of fertility preservation, cryopreservation on-chip has also achieved considerable progress, e.g., on-chip CPA-free cryopreservation of small amounts of human spermatozoa was successfully accomplished (Zou et al, 2013).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Important advantages have been shown compared to traditional selection techniques, such as the potential to work with small sperm sample volumes, short processing times, and the ability to manipulate single cells in a non-invasive manner. In addition, the potential to be a versatile tool for selection applications or fundamental studies on sperm has also been shown [24,32]. Furthermore, the yield of the selected sperm by microfluidic technique was estimated at 41%, what is comparable to the recovery rate of currently used conventional methods [33].…”
Section: Microfluidicsmentioning
confidence: 99%
“…The fact that the epigenetically aberrant sperm populations were preferentially found in men with severe sperm abnormalities and that non-imprinted genes are also affected, suggests that there might be a link between phenotype and epigenotype [4]. However, sometimes normal morphology is not necessarily associated with DNA integrity [24]. Moreover, epigenetic markers had significant variation between samples from different men, as well as significant variation within the same semen sample.…”
Section: Microfluidicsmentioning
confidence: 99%
See 1 more Smart Citation